2017
DOI: 10.1111/ppl.12606
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing transcription for bioproduction in cyanobacteria

Abstract: Sustainable production of biofuels and other valuable compounds is one of our future challenges. One tempting possibility is to use photosynthetic cyanobacteria as production factories. Currently, tools for genetic engineering of cyanobacteria are not good enough to exploit the full potential of cyanobacteria. A wide variety of expression systems will be required to adjust both the expression of heterologous enzyme(s) and metabolic routes to the best possible balance, allowing the optimal production of a parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…These events trigger a change in gene expression pattern, producing multiple cellular responses and allowing the adaptation of the bacterial cell. Therefore, bacterial sigma factors have been emerging as new targets to engineer a wide range of microorganisms (Tripathi et al, 2014;Stensjö et al, 2017). The vast majority of bacterial sigma factors belong to the so-called σ 70 family, due to their similarities with the sigma factor 70 from E. coli (Feklístov et al, 2014;Paget, 2015), but some members of a second family (σ 54 ) have also been identified in a restricted number of bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…These events trigger a change in gene expression pattern, producing multiple cellular responses and allowing the adaptation of the bacterial cell. Therefore, bacterial sigma factors have been emerging as new targets to engineer a wide range of microorganisms (Tripathi et al, 2014;Stensjö et al, 2017). The vast majority of bacterial sigma factors belong to the so-called σ 70 family, due to their similarities with the sigma factor 70 from E. coli (Feklístov et al, 2014;Paget, 2015), but some members of a second family (σ 54 ) have also been identified in a restricted number of bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Promoters are key synthetic biology components in cyanobacteria (Camsund and Lindblad, 2014;Stensjö et al, 2018); a large selection is available, including constitutive, inducible, and repressible promoters and riboswitches Ohbayashi et al, 2016;Videau et al, 2016;Immethun and Moon, 2018;Qiao et al, 2018;Wegelius et al, 2018).A detailed description of the promoter landscape is provided in Box 1, and promoter characteristics are summarized in Table 1 for ease of reference. In addition, ribosome binding sites (Englund et al, 2016;Thiel et al, 2018) and riboregulators, which are RNA sequences that respond to signal nucleic acids to modify expression (Abe et al, 2014b), have been characterized.…”
Section: Promoters and Other Control Elementsmentioning
confidence: 99%
“…This is particularly problematic for modeling, as it interferes with the predictive capability of models. More reactions and major metabolic routes are being discovered even in model species (Xiong et al, 2015;Chen et al, 2016;Zhang et al, 2018), whereas key regulation mechanisms remain more or less unknown Stensjö et al, 2018). Pioneering work in understanding cyanobacterial metabolism, such as the use of transposon libraries to determine essential and beneficial genes (Rubin et al, 2015), as well as advances in metabolic modeling (Nogales et al, 2012;Knoop et al, 2013;Broddrick et al, 2016;Abernathy et al, 2017) provide essential tools for studying metabolism.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…Several hurdles still need to be overcome to expand their commercial viability, most notably, the relatively poor yields compared to heterotrophic bio-platforms (e.g., Escherichia coli and yeast) 7 . The recent expansion of available genetic engineering tools and uptake of the synthetic biology paradigm in cyanobacterial research is helping to overcome such challenges and further develop cyanobacteria as efficient biofactories 8,9,10 .…”
Section: Introductionmentioning
confidence: 99%